PERSEPSI MASYARAKAT DESA TENTANG PUBLIC SPEAKING: IMPLIKASI PADA PEMBELAJARAN BAHASA INDONESIA - Romadlon, Muhammad Rizqi; Suntoko; Nurfadilah, Kurnia Dewi; Asmayanti, Astri (UNIVERSITAS PGRI YOGYAKARTA, 2025)
This study explores rural communities’ perceptions of public speaking by addressing three key aspects: (1) its meaning within the social context as a medium for self-expression and participation; (2) its role in constructing self-confidence through enhanced social support; and (3) its implications for Indonesian language education. Using a qualitative descriptive design, data were collected through in-depth interviews to capture subjective experiences, social meanings, and individual views related to public speaking in daily life. The findings indicate that rural communities regard public speaking as a space for self-expression and social engagement rather than a skill limited to formal settings. Self-confidence is strengthened when supported by the immediate social environment. Integrating public speaking into Indonesian language instruction, particularly speaking skills, should involve opportunities for students to practice in public contexts. In rural settings, public speaking functions not merely as a communicative ability but as a means of reinforcing identity, fostering collaboration, and encouraging active community participation.